2020
DOI: 10.1111/petr.13854
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of nocturnal blood pressure dip and reduction of nocturnal blood pressure with evening anti‐hypertensive medication administration in pediatric kidney transplant recipients: A pilot randomized clinical trial

Abstract: Non-dipping and nocturnal hypertension are commonly found during ABPM in pediatric kidney transplant recipients. These entities are independently associated with increased cardiovascular disease risk in adults. Kidney transplant recipients aged 5-21 years with eGFR > 30 mL/min/1.73 m 2 and ABPM demonstrating nondipping status and normal daytime BP were randomized to intervention (short acting BP medication added in the evening) or control (no medication change) in this pilot, randomized, open-label, blinded en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…In pediatric renal transplant recipients with INH, evening dosing of antihypertensive medication reduced nocturnal BP and restored nocturnal BP dip (51).…”
Section: Treatmentmentioning
confidence: 95%
“…In pediatric renal transplant recipients with INH, evening dosing of antihypertensive medication reduced nocturnal BP and restored nocturnal BP dip (51).…”
Section: Treatmentmentioning
confidence: 95%
“…A pilot study that we conducted found that nighttime administration of hypertension medication restored dipper status in pediatric kidney transplant recipients with no effect on target organ damage markers. 76 3). In the intervention group, nocturnal SBP at 6 months was lower compared to baseline.…”
Section: Which Time Should the Drug Be Administered (Chronotherapy)?mentioning
confidence: 99%
“…Changes of nocturnal BP and non‐dipper status during evening dosing of anti‐hypertensive drugs in pediatric kidney transplant recipients (adapted from Sethna et al 2019) 76 …”
Section: Treatment Of Inhmentioning
confidence: 99%
See 2 more Smart Citations